Thermal Energy Battery with Nano-enhanced PCM - Sheikholeslami Kandelousi, Mohsen (IntechOpen, 2019)
The consumption of any kind of energy has a significant role in protecting energy in the economic development of any country. Today, request in the sector has led to beautiful and large buildings around the world. It is noteworthy that buildings will spend about 30% of the worldwide energy produced. An energy storage system should have certain features that include proper energy storage material with a specific melting temperature at the optimum range, decent heat transfer well, and a pleasant enclosure compatible with the most important energy storage methods. Some features of nano-enhanced phase change materials are presented in this book.